RISK ANALYSIS OF THE DEFICIENCIES FOUND BY THE GMP INSPECTIONS - Yu. V. Podpruznikov; V. N. Shestakov (Разработка и регистрация лекарственных средств, 2019)
A review of GMP-inspections results and the main found deficiencies was carried out. It was established that in the field of inspection of pharmaceutical companies the unresolved problems with the interpretation of the revealed deficiencies are still, i.e. with the objective (a unified, standardized) assigned to these inconsistencies to a criticality levels, which, in turn, affect the regulatory decisions. These problems are current not only to GMP inspections for Commonwealth of Independent States, but also to other inspections (included and not included to PIC/S). The unified procedure of assigning levels of severity with the subsequent completion of the document and its approbation on an international scale was proposed. For processing, ranking and summarize the results of the inspections we used the Pareto analysis for the first time. The results of this analysis allow place right priorities in planning and conducting of GMP-inspections, and for the enterprises - for rational use of the resources to address the causes, to get rid of the dominant issues (critical deficiencies). It was shown that the methodology for ranking of the identified deficiencies with the primary breakdown to the certain categories and followed by their grouping into separate blocks is perspective but needs to be developed and improved in future.